Winter is coming - Johnston, Tony, 1942- (Simon & Schuster Books for Young Readers, 2014)
Each day, from September through November, brings glimpses of forest animals seeking food in preparation for the onset of winter, from a fox sniffing the last apple on the ground to a flock of wild turkeys that finds nothing.